DMX Technologies : assessing the risks amidst rapid expansion - Foo, See Liang (2013)
At the end of 2002, Mr Giang Phung, the Chief Executive of DMX Technologies was assessing the opportunities and the risk exposures of the company he established. The company started operation in 2000 providing network solutions. It instituted the existing core management in early 2001. Focusing on developing its proprietary e-solutions, the company was founded on the philosophy that it should be capable of selecting the best products from different vendors and integrating these into its own value added software solutions for the benefit of its clients.